Understanding Indonesia's Presidential Threshold: A Study on Political Rights - Setiawan, Angga Eka; Fatmawati, Leony; Shulga, Ievgenii (Jurnal Mengkaji Indonesia, 2024)
Abstract: The implementation of the Presidential Threshold in Indonesia's electoral system has significant implications for the nomination process of Presidential and Vice Presidential candidates, impacting political rights and democratic principles. From the experience of Ukraine, where threshold regulations have played a crucial role in shaping the political landscape and ensuring the representation of diverse voices, it is evident that the design and application of such thresholds can have far-reaching consequences on the inclusivity and fairness of electoral processes. By examining the parallels and contrasts between the Indonesian and Ukrainian contexts, valuable insights can be gained into the challenges and opportunities associated with threshold requirements in safeguarding political rights and upholding democratic values. Purpose: This study aims to analyze the setting of the Presidential Threshold in Indonesia, examining its alignment with political rights. It explores the legal framework, historical context, and impact of the Presidential Threshold on the democratic process in Indonesia. By incorporating insights from Ukraine's experience with threshold regulations in electoral processes, the study seeks to draw parallels and contrasts that shed light on the implications for political rights and democratic governance. Understanding how Ukraine has navigated the challenges of setting thresholds to balance legitimacy and inclusivity can provide valuable lessons for Indonesia in enhancing its electoral system and upholding democratic principles. Design/Methodology/Approach: The article employs a normative juridical method, utilizing legal research techniques to analyze relevant laws, constitutional provisions, and court decisions. It also incorporates case approaches, such as the Conceptual Approach and the Statute Approach, to provide a comprehensive understanding of the topic. Findings: The analysis reveals that the Presidential Threshold, as outlined in Article 222 of Law No. 7/2017, establishes a minimum percentage requirement for Presidential and Vice Presidential candidates to be nominated. This threshold has evolved, influencing the electoral landscape and political dynamics in Indonesia. However, concerns are raised regarding its potential contradiction with constitutional principles, particularly concerning political rights and equality in the electoral process. The experience of Ukraine underscores the importance of threshold regulations in strengthening the legitimacy and stability of democratically elected governance while emphasizing the need to preserve political pluralism and inclusivity. Originality/value: This research contributes to the discourse on electoral reform and democratic governance in Indonesia by critically examining the Presidential Threshold. By shedding light on the legal and political dynamics surrounding this threshold, the study provides insights into the challenges and opportunities for enhancing political rights and democratic practices in the Indonesian context.